1998
DOI: 10.1098/rspb.1998.0387
|View full text |Cite
|
Sign up to set email alerts
|

The structure of cynipid oak galls: patterns in the evolution of an extended phenotype

Abstract: Galls are highly specialized plant tissues whose development is induced by another organism. The most complex and diverse galls are those induced on oak trees by gallwasps (Hymenoptera: Cynipidae: Cynipini), each species inducing a characteristic gall structure. Debate continues over the possible adaptive signi¢cance of gall structural traits; some protect the gall inducer from attack by natural enemies, although the adaptive signi¢cance of others remains undemonstrated. Several gall traits are shared by group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
204
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(227 citation statements)
references
References 34 publications
15
204
0
4
Order By: Relevance
“…Related galling insect species usually induce morphologically similar galls on phylogenetically related host plants . Phylogenetic evidence also suggests that gall morphology of aphids (Stern 1995;Inbar et al 2004), thrips (Crespi & Worobey 1998;Morris et al 2002;McLeish et al 2006), sawflies and gall wasps (Stone & Cook 1998;Stone et al 2002;Cook et al 2002) is controlled by the gall inducing organism.…”
Section: Resultsmentioning
confidence: 99%
“…Related galling insect species usually induce morphologically similar galls on phylogenetically related host plants . Phylogenetic evidence also suggests that gall morphology of aphids (Stern 1995;Inbar et al 2004), thrips (Crespi & Worobey 1998;Morris et al 2002;McLeish et al 2006), sawflies and gall wasps (Stone & Cook 1998;Stone et al 2002;Cook et al 2002) is controlled by the gall inducing organism.…”
Section: Resultsmentioning
confidence: 99%
“…Recent phylogenetic analyses of gall-inducing aphids (21), cynipid wasps (22), thrips (23), and sawflies (15) have shown that the insects, not their host plants, determine the location, size, and shape of galls. Thus, gall morphology can be regarded as an extended phenotype [sensu Dawkins (24)] of the galler.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly a thousand species of gall-inducing wasps have been reported (Hymenoptera: Cynipidae: Cynipini) in oak species (Fagaceae: Quercus) (Kinsey 1936, Weld 1960, and they are among the most structurally complex and diverse galls (Liljeblad et al 2008). Gall structures reflect the primary characteristics of the insect inducer, representing an extension of their phenotype (Stone & Cook 1998). The host species of the Cynipini are almost exclusively limited to the Quercus genus (Liljeblad et al 2008), although some use other hosts within the Fagaceae family, such as Castanea, Castanopsis, Lithocarpus and Chrysolepis (Nieves-Aldrey 2001, Stone et al 2002, Liu & Ronquist 2006.…”
mentioning
confidence: 99%
“…During each generation, cynipid species have the ability to induce specific and complex galls on oaks, and in the majority of cases, they form a different gall morphotype each generation (e.g., sexual and asexual). Another characteristic in some species of cynipids is host alternation (heteroecy), which occurs every generation (Askew 1984, Cook et al 1998.…”
mentioning
confidence: 99%